Identification of miRNAs and their targets in two Taraxacum species with contrasting rubber-producing ability - Liang, Cuili; Yan, Yitong; Tan, Yingchao; Yang, Xue; Cao, Jie; Tang, Chaorong; Liu, Kaiye (Frontiers in Plant Science, 2023)
MicroRNAs (miRNAs) are widely involved in various aspects of plant growth and development. However, how miRNAs and their targets regulate natural rubber metabolism remains unclear in the rubber-producing dandelions, which are being developed as alternative commercial sources of natural rubber. Here, we combined small RNA sequencing, degradome sequencing, target gene prediction, and mRNA sequencing to identify miRNAs and their targets in two dandelion species, the high rubber-yielding Taraxacum kok-saghyz (Tk) and the low rubber-yielding T. spadiceum (Ts). A total of 142 miRNAs, including 108 known and 34 novel ones, were discovered, with 53 identified as differentially expressed (DE) between the latex of Tk and Ts. Degradome sequencing identified 145 targets corresponding to 74 miRNAs. TAPIR and psRNATarget, respectively, predicted 165 and 164 nonredundant targets for the 53 aforementioned DE miRNAs. Gene ontology (GO) enrichment analysis indicated the DE miRNAs and their targets might affect natural rubber production via regulating macromolecular biosynthesis and metabolism in latex. Four critical types of regulatory modules, including miR172-AP2/ERF, miR164-NAC, miR160-ARF, and miRN19-protein kinase, were identified and their interaction networks were constructed, indicating a potential involvement in natural rubber production. The findings and the large miRNA dataset presented here are beneficial to further deciphering the roles of miRNAs in the biosynthesis of natural rubber and medicinal metabolites in dandelion.